Obstipation – Pathophysiologie, Diagnostik, Behandlung - Müller-Lissner, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2019)
The most relevant risk factors for the development of chronic constipation are neurologic disorders such as Parkinson’s disease, immobility, and some drugs, in particular opioids. A proctologic exam and exclusion of red flags form part of the basic assessment. The currently available laxatives are effective and safe, habituation and tolerance (tachyphylaxis) being an exception. Also long-term intake of laxatives is of no concern when taken in recommended doses (no relevant hypokalemia!). Though the newer compounds (e. g., prucalopride, linaclotide, lubiprostone) are not more effective than the older ones, developing new drugs with alternative mode of action is reasonable since there are patients not satisfied with the currently available substances. Macrogol, Bisacodyl, and sodium picosulfate are the laxatives of first choice. Their selection depends on the individual preference of the patient. Opioids often induce constipation which can be ameliorated by laxatives or PAMORAs (peripherally acting µ-opioid antagonists).
Keywords: Obstipation; Laxanzien; gastrointestinale Motilität; Ballaststoff